2002
DOI: 10.1034/j.1600-0404.2002.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis function and cytokine production in multiple sclerosis with or without interferon-β treatment

Abstract: In MS the HPA axis function seems normal and not influenced by IFN-beta treatment. This result is discussed in relation to the increased production of pro-inflammatory cytokines found in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
(44 reference statements)
1
13
0
1
Order By: Relevance
“…26 No.12 December 2005 results with diminished [17] or normal cortisol-suppression after dexamethasone [18,19].…”
Section: In Vivo Imaging Of Multiple Sclerosis Pathologymentioning
confidence: 99%
“…26 No.12 December 2005 results with diminished [17] or normal cortisol-suppression after dexamethasone [18,19].…”
Section: In Vivo Imaging Of Multiple Sclerosis Pathologymentioning
confidence: 99%
“…Free radicalinduced lipid peroxidation is believed to play an important role in the pathogenesis of this secondary injury (4,5,24,25,26). But, as lipid peroxidation was demonstrated experimentally to reach peak values immediately after SCI, they appear to be unsuitable targets for pharmacological treatment of SCI in clinical practice (27). Thus, there is a clear and urgent need for a neuroprotective agent with proven effi cacy and minimal risk of side effects and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Goebel et al (46) have shown that in patients with MS long-term treatment with IFN beta had no effect on activity of the hypothalamic-pituitary-adrenal (HPA) axis and did not alter the patients' mood states. In another study, IFN beta administered to patients with MS had no significant effect on HPA axis (47 …”
Section: Mood-related Symptomsmentioning
confidence: 93%